PREVALENCIA DE CARCINOMA EPIDERMOIDE PULMONAR Y DE ADENOCARCINOMA PULMONAR EN EL HOSPITAL RAFAEL ÁNGEL CALDERÓN GUARDIA 2001-2006 - Mora Solano, Simón (2012)
The pulmonary adenocarcinoma is the  more common  lung cancer, in women and in nonsmokers in both sexes. Its incidence is increasing. In industrialized countries like the United States, is now the leading cause of cancer death in women, in part because of the decline in mortality from breast and colorectal cancer, because of the implementation of preventive measures and health programs in the last decade. It is estimated that in 2009 twice as many women died of lung adenocarcinoma from breast cancer in that country. This increase in mortality from lung cancer in recent years in women is mainly due to the increase in this histological type of adenocarcinoma.